Analisis Faktor-Faktor yang Mempengaruhi Loyalitas Nasabah Bank Syariah: (Studi Pada Bank Muamalat Tbk. Cabang Gorotalo) - Mustofa Mustofa (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
The purpose of this study are: (1) To determine and analyze the influence of service quality, complaint handling, and corporate image partially on customer loyalty. (2) To determine and analyze the influence factors of service quality, complaint handling, and image simultaneously on customer loyalty. This study is a survey, the research done on large or small populations. The population of this research is all bank customers Muamalat branch Gorontalo and customers as sample of 100 people. Technical analysis of data using multiple regression using SPSS 22.0.The study results showed that the quality of service and complaint handling significant effect on customer loyalty, while the image of the company has no significant effect on customer loyalty. As for quality of service, complaint handling and image simultaneously significant effect on customer loyalty of Islamic banks in Gorontalo.